Mentoring K Scholars: Strategies to Support Research Mentors - Burnham, Ellen L. (Blackwell Publishing Inc, 2011)
The goal of this paper is to present strategies utilized to support K scholar research mentors. K scholars are generally assistant professors who are close to developing independent research programs. Of all the various types of mentees, K scholars offer the greatest challenges, as well as the greatest rewards, for research mentors. To see one’s mentee achieve independent PI status and become an established investigator is one of the great joys of being a research mentor. Research mentors for K scholars, however, may not directly benefit from their mentoring relationship, neither in terms of obtaining data to support their research program or laboratory, nor in assistance with grants or scientific papers. There is a pressing need for the research community to address the workload, institutional expectations, and reward system for research mentors. The dearth of research mentors and role models in clinical translational science parallels the decreasing number of physicians choosing careers in clinical research. While there is limited empirical information on the effectiveness of mentor support mechanisms, this white paper concludes that providing mentor support is critical to expanding the available pool of mentors, as well as providing training opportunities for K scholars. Clin Trans Sci 2011; Volume 4: 199–203